A model for business performance improvement: a case of the postal company - Lazarević, Dragan; Dobrodolac, Momčilo; Švadlenka, Libor; Stanivuković, Bojan (Journal of Business Economics and Management, 2020)
The aim of this paper is to propose a management model which would assess the state of the business and indicate the improvement points, as well as to demonstrate the applicability of the model in a case of the postal company. An A’BA model is proposed which represents a combined application of Analytic Hierarchy Process – AHP method as a multi-criteria decision making tool and theory of business areas. The research consists of two parts. To define the most important influencing factor on business performance, the experts are interviewed. A new concept is proposed and applied in the process of aggregating experts’ assessments based on their mapping in a plane. This creates the appropriate surface, and the position of its centroid in relation to the Saaty’s scale defines the final score of pairwise comparison - an indicator of the relationship between two elements that are compared. In the second part, additional experts from the determined area are involved to define an approach for detailed analysis of the most important factor. In this case, the approach included a survey of employees based on the specialized questionnaire. The guidelines for business performance improvement are obtained.